Selenium and iodine status in the Kurdistan region of Iraq - Karim, Abdolbaset (2018)
The primary aims of this project were to: i) provide a survey of selenium and iodine concentrations in the terrestrial environment and locally grown crops of Iraqi-Kurdistan; ii) gain greater understanding of the factors controlling bioavailability of these elements in the calcareous soils of the region; iii) investigate the feasibility of biofortification of selenium and iodine and test the use of isotopically enriched tracers for this purpose; iv) assess iodine and selenium dietary intake and nutritional status of the local population using dietary questionnaires and a survey of a human biomarker. A survey was conducted covering locally grown crops, matched soil samples and irrigation water including 300 plant, 100 soil and 20 water samples. The potential availability of Se and I for plant uptake was examined by quantifying the soluble and adsorbed fractions of both micronutrients and their species. The influences of soil factors on plant Se and I uptake were examined. Results indicated that total soil Se (SeTot = 309 µg kg-1) was lower than the global average (400 µg kg-1). Approximately 2.5% of soil Se was present in the soluble and adsorbed fractions with an equal proportion of selenate and selenite in the soluble fraction and mainly selenite in the adsorbed fraction. The organically-bound Se extractability ranged from 20-89% of SeTot, depending on soil pH. Plant Se content was variable between crop species and different areas within Kurdistan with mean concentration of 113,112, 69 and 49 µg kg-1dw for leafy vegetables, tubers, fruit vegetables and wheat grain respectively. Higher plant Se concentrations were observed in plants grown in soils with pH>8. The mean concentration of total soil iodine was 4140 µg kg-1. Almost 10% of this value was present in the soluble and adsorbed fractions. Mean plant iodine concentrations were 439, 368, 140, and 12 µg kg-1dw for leafy vegetables, fruit vegetables, tubers and grains respectively. The combined concentrations of soluble and adsorbed iodine were correlated with plant iodine content. The mean concentrations of irrigation water Se and I were 0.495 and 11.9 µg L-1 respectively. The amount (%) of soil CaCO3 was strongly correlated with iodine concentration in groundwater used for irrigation and irrigation water iodine concentration was again strongly correlated with plant iodine concentrations. The feasibility of Se biofortification in calcareous soils using local vegetable genotypes from Kurdistan was examined using 10 g ha-1 77Se as a biofortification treatment (and isotopic tracer). Five commonly used vegetables, including celery, chard, lettuce, radish and spring-onion were planted in soils spiked with the 77Se application and grown for 8 weeks under controlled growth room conditions. Results indicated that, at the end of the growth period approximately 35% of applied 77Se had been transferred to a recalcitrant form in the soil which resisted extraction with 10% TMAH. Only 5% of 77Se was present within the soluble and adsorbed soil fractions combined, at harvest. The amount of 77Se taken up by plant biomass varied according to crop species; 25% for radish and 7-8% for other vegetables from the total 77Se applied. Plant 77Se concentrations varied despite growing in identical soils and, unexpectedly, plants contained more Se originating from the soil rather than the fertilizer. The ratio of Sesoil/Sefertilizer also varied between varieties reflecting different growth patterns and uptake rates against a backdrop of decreasing fertilizer Se availability during the growing season. Biofortification of iodine using a range of vegetable crops grown in calcareous soil was investigated, using soil and vegetable genotypes from Kurdistan, and employing 129I as a tracer. Vegetables were irrigated daily with water containing 5.56 and 6.89 µg L-1 129IO3- and 129I- respectively for 8 weeks. Total and fractionated iodine (127I and 129I) was conducted on moist soil (c. field capacity) and air dried soil at the end of the growing season. Plant analysis was also undertaken for 127I and 129I, using ICP-MS. Results showed that plant iodine concentrations originating from native soil iodine were variable even when grown in identical soils. Generally, iodine concentrations in roots was greater than in shoots for both 127I and 129I. Vegetables irrigated with 129I- (iodide) had considerably lower iodine concentrations (6.2-12 µg kg-1dw) than those irrigated with 129IO3- (iodate) (53.3-479 µg kg-1dw). The majority of plant iodine originated from soil iodine rather than fertilizer iodine and varied depending on 129I species applied (iodate or iodide) and the vegetable plant type grown. For vegetable shoots treated with 129I- (iodide) only 3% of the iodine of the three test plants originated from the 129I treatment. By contrast, for 129IO3- (iodate) applications 11, 22 and 58% of iodine in the shoots of celery, lettuce and chard were from the 129I additions respectively. The recovery rate of 129I from soil extracted with 10% TMAH ranged from 63-95% of total iodine applied and varied depending on vegetable variety. The 129I recoveries from pots irrigated by 129IO3- were less than from 129I- irrigated soils suggesting greater loss of iodine from the iodate irrigated system. To assess the Se and I status of the population in a region of Kurdistan, the food composition data and dietary intake of Se and I was determined for 410 volunteers using a semi- quantitative food questionnaire, including commonly used food items. To directly investigate level of nutritional status of Se and I, urine samples were also collected from each participants as a biomarker. Daily dietary intake and source apportionment of Se and I from each food item was determined using questionnaire survey. The daily intake of I from food excluding salt was 119 µg d-1. Vegetables and fruits supplied 48%, protein sources 25%, cereal and grains 9%, dairy products 8% and water 2% of daily I intake. The majority (>90%) of salt samples collected were iodised with a mean I concentration of 40 mg kg-1 and daily intake of salt was estimated as 13.5g d-1. Accounting for salt intake, average daily iodine intakes increased to 668 µg d-1, with salt supplying 82% of daily I intake. The median urinary iodine (corrected for creatinine) was 379 µg g-1CRT and 424 µg L-1 osmolality corrected. More than 90% of school age children and over 55% all participants had excessive I intake according to WHO classification. The salt I concentration consumed by each family was highly correlated with mean urinary iodine of family members. Urinary Na and I were also correlated. The iodine intake estimated according to salt intake (calculated based on urinary Na) was strongly correlated with iodine intake calculated according to urinary iodine. The daily salt intake estimated by urinary Na was 15.3 g d-1 considerably higher than WHO recommended. Mean total daily intake of Se according to the questionnaire responses was 72.9 µg d-1 with 21% of participants having a daily intake lower than recommended RDA. The mean urinary Se fell in the range of 21.2-24.8 µg L-1 depending on justification methods. The predicted Se intake from urinary Se gave a values of 59 and 42 µg d-1 according to the method used which may imply Se deficiency. To conclude, Kurdistan soils Se content was found insufficient. Despite that, Due to high pH effect in some areas plant Se content seems to be having considerably higher Se content rather than areas with lower pH. Later studies revealed that daily Se intake may not enough to address the Se requirement of population. Biofortification of Se possible but to prevent decreasing availability would be recommend to apply in med season or foliar application. Typically soil and plant of Kurdistan found in a minimum of normal range of iodine and comparable with other areas. Irrigation water was found as a main source of plant iodine uptake. The daily iodine intake from food excluding salt is not enough to meet the recommended iodine level but considering high consumption of iodized salt in that region it can be classified as an excessive iodine intake which could cause high intake iodine consumption disorders such as hyperthyroidism and in turn health issues caused by elevated Na intake such as cardiovascular disease. In current iodine nutritional status of the region plant biofortification would not be recommended.